The prevalence, posttraumatic depression and risk factors of domestic child maltreatment in rural China: A gender analysis. (September 2020) - Wan, Guowei; Tang, Sisi; Xu, Yicheng
Highlights: The gender disparities in DCM vary among different maltreatment subtypes. DCM's negative effect was more severe for girls than for boys. Gender heterogeneity is less evident than gender homogeneity in the risk factors. Abstract: Objective: Currently, gender disparities in domestic child maltreatment (DCM) have become an important and highly controversial issue worldwide. This study aims to provide panoramic evidence from China on this issue. Method: Data were derived from a survey of 4, 308 children ( M age = 12.13, 48.7% were boys) conducted in seven provinces in rural China from June to December 2019. This study used multistage cluster sampling to select respondents, and modified versions of the JVQ Scale and the DSM-5 Scale (11–17 years old) were adopted. Results: This study reached three significant conclusions. First, the gender disparities in DCM vary among different maltreatment subtypes. Compared with girls, boys are more likely to experience physical abuse. A higher prevalence of neglect is observed among girls than among boys. Second, although DCM significantly increased the likelihood of posttraumatic depression for all children, its negative effect was more severe for girls than for boys. Third, gender heterogeneity is less evident than gender homogeneity in the risk factors for DCM. In rural China, children's problematic behaviours, family structure, parents' experiences of childhood violence and family relationships are common predictors of maltreatment for all children. Conclusion: This paper highlights gender differences in the risk of DCM among children in rural China, reveals the Confucian culture behind DCM and gender, and provides Chinese evidence for building an international dialogue.